Recent developments in phase change material-based solar water heating systems: Insights on research trends and opportunities - Itamar Harris; Arthur James Rivas; Maria De Los Angeles Ortega Del Rosario; M. Ziad Saghir (International Journal of Thermofluids, 2023)
Numerous researchers have proposed phase change materials (PCMs) as an alternative for increasing the autonomy of solar water heaters (SWHs). Many studies have considered SWHs with PCMs in three main configurations: PCMs inside the solar thermal collector, inside a coupled heat storage unit, and within the water storage tank. A wide range of topics has been explored within studies assessing SWHs with PCMs in recent years, including but not limited to enhancement techniques for improving heat transfer, optimization strategies, economic factors, weather exposure on performance, and the application of design methodologies. This article reviews and discusses recent work on these trending topics, identifies research opportunities, and suggests promising research efforts toward more mature SWHs with PCM technology, focusing on long-term performance, scalability, economic, and technical feasibility.